A chemically fuelled self-replicator - Sarah M. Morrow (Nature Portfolio, 2019)
Understanding how simple chemical mixtures transition into truly emergent systems is essential to create new lifelike materials. Here, the authors show a self-replicating system that can be maintained out-of-equilibrium by an oxidant fuel in analogy to simple metabolic cycles.